Higher Education Reform: Necessary, Urgent, and Complex (Observatorio Económico, 2013)
Higher education, and university education in particular, is for most families an aspirational goal, the cradle of and the source of answers to many of their most pressingsocial and economic problems. Hence the importance of building a system that offers equal opportunity of access to quality higher education, one capable of meeting the expectations it has raised. Education policy in this area, however, falls far short of that objective. Continue reading...
Keywords: Higher education; Education reform; Quality education